The Correlation between Work Barrier with Employee’s Discipline on Occupational Safety and Health - Rachma Noor Kafila; Popy Puspitasari; Ratna Dwi Wulandari (The Indonesian Journal of Occupational Safety and Health, 2020)
Introduction: Hospital as one of the health services in Indonesia is required to implement the development of human resources or health workers in health services. Conducting hospital coach should be specific to build on certain aspects. The coaching can be done by looking at aspects that are lacking in the assessment of human resources. Wiyung Sejahtera Surabaya Hospital has a decision of discipline that decreased from year to year. Researcher needed see any factor that can lead to low employees’ discipline. One factor that can contribute was the job barrier felt by the employees. This study aimed to determine the relationship of work barriers as one of the employees’ benchmark in the hospital on the employees’ performance level at Wiyung Sejahtera Surabaya Hospital. Method: The type of this research was quantitative research with an analytic observational method. Based on the time, this research used a cross-sectional design. The population in this study was the employees of Wiyung Sejahtera Surabaya hospital with 80 samples taken through proportional sampling technique. The independent and dependent variables of this research were work barriers and work discipline. Data were analyzed using Kendall's tau-b test to determine the correlation between the two variables. Results: The results obtained that the work barrier had a negative significant correlation to the discipline of employees in the Wiyung Sejahtera Surabaya hospital. The higher the obstacle of work owned by employees in the hospital, the lower the discipline of the employees. Conclusion: The barriers can lower the discipline of employees at the hospital.Keywords: discipline, occupational health and safety, work barriee